Aggregation of Platelets and Inert Particles Induced by Thrombin - Chao, Frangis C.; Tullis, James L.; Conneely, Gail S.; Lawler, John W. (Thrombosis and Haemostasis, 1976)
Thrombin-induced platelet aggregation and release were investigated in washed platelet suspensions and in suspensions of inert particles in order to evaluate the role of fibrinogen-fi-brin transformation in aggregometer tracings. Thrombin (0.25–2.0 U/ml) produced two waves of light transmission increase (LTI) in both platelet and inert particle suspensions containing fibrinogen, and concomittantly aggregates were observed under phase microscopy. Without fibrinogen, thrombin induced rapid release of platelet ADP but failed to cause second wave of LTI. The kinetics of LTI in platelet and inert particle systems were related to both thrombin and fibrinogen concentrations. A rapid second wave of LTI could be produced by direct interaction of thrombin-treated platelets or inert particles with polymerizing fibrin, and was inhibited by sodium sulfite and low pH of 5.1 which prevent fibrin monomer polymerization. No fibrin strands were noted in platelet aggregates fixed at the completion of the second wave of LTI. Apyrase and PGE1 inhibited the rate of first but not that of second wave LTI. The results suggest that the release of platelet ADP induced by thrombin primarily affects the first phase aggregation, and the second phase may result from interaction of thrombin-exposed platelets and polymerizing fibrin. Thus, the blood coagulation mechanism may be directly involved in platelet aggregation.